Synthesis and Characterization of Co(II), Ni(II), Cu(II) and Zn(II) Complexes of Glyoxime Hydrazone - Sarikavakli, N.; Cakici, H.T. (Asian Journal of Chemistry, 2010)
A novel ligand, (1E,2E)-2-(hydroxyimino)-N'-[(1E)-2-oxo-2-phenylethylidene]ethanehydroximohydrazide (LH2) was prepared by reacting anti-glyoxime hydrazine with phenylglyoxal monohydrate in absolute ethanol. On the basis of the magnetic and spectral evidences a square planar geometry for Co(II), Cu(II) and Ni(II) complexes and a tetrahedral geometry for Zn(II) complex are proposed. The ligand and its Co(II), Ni(II), Cu(II) and Zn(II) complexes were determined by elemental analyses, magnetic susceptibility, molar conductance, thermogravimetric analysis (TGA) and spectroscopic (UV-Vis, FT-IR 1H and 13C NMR) data.